1976
DOI: 10.1111/j.1365-2621.1976.tb01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antemortem Environmental Temperatures on Postmortem Glycolysis and Tenderness in Excised Broiler Breast Muscle

Abstract: The effects of heat stress (38"C), cold stress (4OC) and extreme cold stress (-20°C) before slaughter on the tenderness and postmortem glycolysis of the excised chicken breast muscle were studied. Heat stress significantly (p < 0.05) increased the toughness of breast muscle. Though statistically not significant, cold stress also adversely affected the tenderness. The heat-stressed birds showed higher zero hr glycogen, higher zero hr pH and significantly (p < 0.05) lower ultimate pH than the controls. The cold-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…kg −1 muscle, which corresponds closely with the glycolytic potential (mean) of 108.1 LA eq. kg −1 muscle reported Berri et al 31 and with the initial glycogen content of 52.8 mmol kg −1 muscle found Lee et al 32 In the present study, the initial glycogen content of chicken PS muscle was twice that of QF muscle, but Warriss et al 5 have reported as much as a three-fold difference between muscle types. A significant negative relationship existed between pH u and glycolytic potential in both muscles, but the correlations were lower than those Lee et al 32 found in chicken PS muscle (r = −0.78).…”
Section: The Ultimate Ph and Glycolytic Potential Of Chicken Musclescontrasting
confidence: 49%
“…kg −1 muscle, which corresponds closely with the glycolytic potential (mean) of 108.1 LA eq. kg −1 muscle reported Berri et al 31 and with the initial glycogen content of 52.8 mmol kg −1 muscle found Lee et al 32 In the present study, the initial glycogen content of chicken PS muscle was twice that of QF muscle, but Warriss et al 5 have reported as much as a three-fold difference between muscle types. A significant negative relationship existed between pH u and glycolytic potential in both muscles, but the correlations were lower than those Lee et al 32 found in chicken PS muscle (r = −0.78).…”
Section: The Ultimate Ph and Glycolytic Potential Of Chicken Musclescontrasting
confidence: 49%
“…Drip loss from breast meat and cooking loss from leg meat can also be higher (Debut et al, 2003;Mujahid, Akiba, & Toyomizu, 2007;Northcutt et al, 1994;Petracci, Fletcher, & Northcutt, 2001). Some, but not all studies have shown that breast meat can be tougher following pre-slaughter heat stress, or that it may develop a stronger rigor (Lee et al, 1976;Wood & Richards, 1975). There has been no consistent effect on breast meat a à value when considering all the experiments, and no effect has been seen on heat-stable pinkness (Nagle, et al, 2000).…”
Section: Poultry Meat Qualitymentioning
confidence: 90%
“…The other approach is to examine the effects of environmental conditions experimentally. In extreme situations both heat stress and exercise can influence muscle metabolism and meat quality (Lee, Hargus, Hagberg, & Forsythe, 1976;Ngoka & Froning, 1982). Quantitative relationships can then be used in models that apply to a sector of the industry.…”
Section: Predicting Future Changes In Meat Quality and Safetymentioning
confidence: 99%
“…Not only is the post-mortem biochemistry of these muscles changed, but consequently the overall quality, palatability and shelf life (use by date) of the meat is altered (Hendricks 1965;Fraser et al 1966;Lee et al 1976; Lewis et al 1981;Sikorski et al 1990;Lowe et al 1993;Sigholt et al 1997;Abdalla et al 1999;Diouf & Rioux 1999). There are numerous studies on spoilage and storage effects in the muscles of crustaceans (Sidhu et al 1974;Stroud et al 1982;Ashie et al 1996;Chinivasagam et al 1996;Shimada et al 2000;Mendes et al 2001;Aubourg et al 2007), but there is very little knowledge of the way in which ante-mortem stressors change the post-mortem biochemistry, and hence quality of related shellfisheries products.…”
Section: Introductionmentioning
confidence: 99%